PROFESSIONAL COMMUNITIES AND HIGH SCHOOL: TO FIND INTERACTION - M. V. Artamonova; I. A. Lambaeva (Научный вестник МГТУ ГА)
Discusses the issue of development of professionally-oriented educational programs on the basis of requirements for the competence of graduates of higher educational institutions as a way to improve the quality of education and higher education model adaptation to modern conditions. Analyzes the experience of interaction between higher education institutions and professional associations in the formation of professional standards.